Improved C5D Electronic Realization of Conductivity Detector for Capillary Electrophoresis - Jaanus, Martin; Udal, Andres; Kukk, Vello; Umbleja, Kadri; Gorbatsova, Jelena; Molder, Lauri (Elektronika ir Elektrotechnika, 2016)
The axial C4D (Capacitively Coupled Contactless Conductivity Detection) measurement electronics for capillary electrophoresis is considered and a new improved C5D compensated detection concept is proposed and tested. Using the idle compensation channel with inversed signal and immediate analogue summation of the active and idle channel currents yields effective suppression of the influence of the parasitic stray capacitance. Preliminary experiments have confirmed at least three-fold improvements of measurement resolution. Realisation of electronics allows flexible tuning of frequency from 0.2 MHz to 2 MHz. The relatively high voltage supply of 15 V for the AC measurement units together with 24-bit accurate analogue-to-digital converter yields additional improvement for the sensitivity. DOI: http://dx.doi.org/10.5755/j01.eie.22.3.15311